At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Let's find the composition of functions given [tex]\( f(x) = \sqrt[3]{x-4} \)[/tex] and [tex]\( g(x) = x^3 + 4 \)[/tex].
### (a) [tex]\( f \circ g \)[/tex]
The composition [tex]\( f \circ g \)[/tex] is defined as [tex]\( f(g(x)) \)[/tex].
1. Start with [tex]\( g(x) = x^3 + 4 \)[/tex].
2. Substitute [tex]\( g(x) \)[/tex] into [tex]\( f \)[/tex]:
[tex]\[ f(g(x)) = f(x^3 + 4) \][/tex]
3. Now, use the definition of [tex]\( f(x) \)[/tex] which is [tex]\( f(x) = \sqrt[3]{x - 4} \)[/tex]:
[tex]\[ f(x^3 + 4) = \sqrt[3]{(x^3 + 4) - 4} \][/tex]
4. Simplify the expression inside the cube root:
[tex]\[ f(x^3 + 4) = \sqrt[3]{x^3} \][/tex]
5. The cube root of [tex]\( x^3 \)[/tex] is [tex]\( x \)[/tex]:
[tex]\[ f(x^3 + 4) = x \][/tex]
So,
[tex]\[ f \circ g = x \][/tex]
### Testing [tex]\( f \circ g \)[/tex] at [tex]\( x = 2 \)[/tex]:
[tex]\[ f \circ g (2) = 2 \][/tex]
Thus,
[tex]\[ f \circ g (2) = 2.0 \][/tex]
### (b) [tex]\( g \circ f \)[/tex]
The composition [tex]\( g \circ f \)[/tex] is defined as [tex]\( g(f(x)) \)[/tex].
1. Start with [tex]\( f(x) = \sqrt[3]{x-4} \)[/tex].
2. Substitute [tex]\( f(x) \)[/tex] into [tex]\( g \)[/tex]:
[tex]\[ g(f(x)) = g(\sqrt[3]{x-4}) \][/tex]
3. Now, use the definition of [tex]\( g(x) \)[/tex] which is [tex]\( g(x) = x^3 + 4 \)[/tex]:
[tex]\[ g(\sqrt[3]{x-4}) = (\sqrt[3]{x-4})^3 + 4 \][/tex]
4. Simplify the expression:
[tex]\[ (\sqrt[3]{x-4})^3 = x - 4 \][/tex]
5. Thus,
[tex]\[ g(\sqrt[3]{x-4}) = (x - 4) + 4 \][/tex]
6. Simplify the expression:
[tex]\[ g(\sqrt[3]{x-4}) = x \][/tex]
So,
[tex]\[ g \circ f = x \][/tex]
### Testing [tex]\( g \circ f \)[/tex] at [tex]\( x = 2 \)[/tex]:
[tex]\[ g \circ f (2) = g(\sqrt[3]{2 - 4}) = g(\sqrt[3]{-2}) \][/tex]
[tex]\[ g(\sqrt[3]{-2}) = (\sqrt[3]{-2})^3 + 4 = -2 + 4 = 2 \][/tex]
[tex]\[ g \circ f (2) = 2 + 6.661338147750939 \times 10^{-16} \imath \][/tex]
Thus,
[tex]\[ g \circ f (2) = 2 + 6.661338147750939 \times 10^{-16} \imath \][/tex]
### (c) [tex]\( g \circ g \)[/tex]
The composition [tex]\( g \circ g \)[/tex] is defined as [tex]\( g(g(x)) \)[/tex].
1. Start with [tex]\( g(x) = x^3 + 4 \)[/tex].
2. Substitute [tex]\( g(x) \)[/tex] into itself:
[tex]\[ g(g(x)) = g(x^3 + 4) \][/tex]
3. Now, use the definition of [tex]\( g(x) \)[/tex]:
[tex]\[ g(x^3 + 4) = (x^3 + 4)^3 + 4 \][/tex]
4. Simplify inside the expression:
When evaluated at [tex]\( x = 2 \)[/tex]:
[tex]\[ g(x) = 2^3 + 4 = 8 + 4 = 12 \][/tex]
[tex]\[ g(g(2)) = g(12) = 12^3 + 4 = 1728 + 4 = 1732 \][/tex]
So,
[tex]\[ g \circ g = 1732 \][/tex]
Therefore, the compositions are:
[tex]\[ \begin{aligned} (a) & \quad f \circ g (2) = 2.0 \\ (b) & \quad g \circ f (2) = 2 + 6.661338147750939 \times 10^{-16} \imath \\ (c) & \quad g \circ g (2) = 1732 \\ \end{aligned} \][/tex]
### (a) [tex]\( f \circ g \)[/tex]
The composition [tex]\( f \circ g \)[/tex] is defined as [tex]\( f(g(x)) \)[/tex].
1. Start with [tex]\( g(x) = x^3 + 4 \)[/tex].
2. Substitute [tex]\( g(x) \)[/tex] into [tex]\( f \)[/tex]:
[tex]\[ f(g(x)) = f(x^3 + 4) \][/tex]
3. Now, use the definition of [tex]\( f(x) \)[/tex] which is [tex]\( f(x) = \sqrt[3]{x - 4} \)[/tex]:
[tex]\[ f(x^3 + 4) = \sqrt[3]{(x^3 + 4) - 4} \][/tex]
4. Simplify the expression inside the cube root:
[tex]\[ f(x^3 + 4) = \sqrt[3]{x^3} \][/tex]
5. The cube root of [tex]\( x^3 \)[/tex] is [tex]\( x \)[/tex]:
[tex]\[ f(x^3 + 4) = x \][/tex]
So,
[tex]\[ f \circ g = x \][/tex]
### Testing [tex]\( f \circ g \)[/tex] at [tex]\( x = 2 \)[/tex]:
[tex]\[ f \circ g (2) = 2 \][/tex]
Thus,
[tex]\[ f \circ g (2) = 2.0 \][/tex]
### (b) [tex]\( g \circ f \)[/tex]
The composition [tex]\( g \circ f \)[/tex] is defined as [tex]\( g(f(x)) \)[/tex].
1. Start with [tex]\( f(x) = \sqrt[3]{x-4} \)[/tex].
2. Substitute [tex]\( f(x) \)[/tex] into [tex]\( g \)[/tex]:
[tex]\[ g(f(x)) = g(\sqrt[3]{x-4}) \][/tex]
3. Now, use the definition of [tex]\( g(x) \)[/tex] which is [tex]\( g(x) = x^3 + 4 \)[/tex]:
[tex]\[ g(\sqrt[3]{x-4}) = (\sqrt[3]{x-4})^3 + 4 \][/tex]
4. Simplify the expression:
[tex]\[ (\sqrt[3]{x-4})^3 = x - 4 \][/tex]
5. Thus,
[tex]\[ g(\sqrt[3]{x-4}) = (x - 4) + 4 \][/tex]
6. Simplify the expression:
[tex]\[ g(\sqrt[3]{x-4}) = x \][/tex]
So,
[tex]\[ g \circ f = x \][/tex]
### Testing [tex]\( g \circ f \)[/tex] at [tex]\( x = 2 \)[/tex]:
[tex]\[ g \circ f (2) = g(\sqrt[3]{2 - 4}) = g(\sqrt[3]{-2}) \][/tex]
[tex]\[ g(\sqrt[3]{-2}) = (\sqrt[3]{-2})^3 + 4 = -2 + 4 = 2 \][/tex]
[tex]\[ g \circ f (2) = 2 + 6.661338147750939 \times 10^{-16} \imath \][/tex]
Thus,
[tex]\[ g \circ f (2) = 2 + 6.661338147750939 \times 10^{-16} \imath \][/tex]
### (c) [tex]\( g \circ g \)[/tex]
The composition [tex]\( g \circ g \)[/tex] is defined as [tex]\( g(g(x)) \)[/tex].
1. Start with [tex]\( g(x) = x^3 + 4 \)[/tex].
2. Substitute [tex]\( g(x) \)[/tex] into itself:
[tex]\[ g(g(x)) = g(x^3 + 4) \][/tex]
3. Now, use the definition of [tex]\( g(x) \)[/tex]:
[tex]\[ g(x^3 + 4) = (x^3 + 4)^3 + 4 \][/tex]
4. Simplify inside the expression:
When evaluated at [tex]\( x = 2 \)[/tex]:
[tex]\[ g(x) = 2^3 + 4 = 8 + 4 = 12 \][/tex]
[tex]\[ g(g(2)) = g(12) = 12^3 + 4 = 1728 + 4 = 1732 \][/tex]
So,
[tex]\[ g \circ g = 1732 \][/tex]
Therefore, the compositions are:
[tex]\[ \begin{aligned} (a) & \quad f \circ g (2) = 2.0 \\ (b) & \quad g \circ f (2) = 2 + 6.661338147750939 \times 10^{-16} \imath \\ (c) & \quad g \circ g (2) = 1732 \\ \end{aligned} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.